2018
DOI: 10.3390/ijerph15122873
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, Distribution, Sources and Ecological Risk Assessment of Trace Elements in Soils from Wuhan, Central China

Abstract: This study aimed to determine the concentration levels, potential sources and ecological risks of eleven trace elements, namely Cr, Fe, Co, Ni, Cu, As, Sb, Cd, Zn, Hg and Pb, in the soil from Huangpi district, Wuhan, Central China. Soil samples were collected from eighteen sites at soil depths of 1–10 and 10–20 cm and analyzed using Inductively Coupled Plasma-Mass Spectrometer ICP-MS (Thermo X SERIES 2, Scientific and Innovative Technology Co. Ltd., Beijing, China). The recorded mean concentration of the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…However, only the concentration of Cd in Wuhan was significantly higher than those in other cities (Table S5) and 25.7 times higher than the local background value (Table 1). Previous studies had already supported that Cd had a relatively higher concentration in Wuhan (Tadesse et al, 2018). As…”
Section: Heavy Metal Concentration In Campus Dustmentioning
confidence: 74%
“…However, only the concentration of Cd in Wuhan was significantly higher than those in other cities (Table S5) and 25.7 times higher than the local background value (Table 1). Previous studies had already supported that Cd had a relatively higher concentration in Wuhan (Tadesse et al, 2018). As…”
Section: Heavy Metal Concentration In Campus Dustmentioning
confidence: 74%
“…The southwestern and northeastern regions of the study area are densely populated areas with heavy traffic; the spatial distribution map showed that Pb was significantly enriched in these two areas. Pb was the main traffic token [54], as Pb is released from the tail gas emissions after gasoline combustion, and the wear on automobile engines during braking and the use of catalysts produce lead emissions [55][56][57]. Once all cars used leaded gasoline.…”
Section: Pc3: Pbmentioning
confidence: 99%
“…Currently, Hakanson's potential ecological risk index method (Hakanson 1980) is predominantly used in ecological risk assessments, but, in order to use it correctly in assessments, the potential ecological risk coefficient (E) and potential ecological risk index (RI) grading standards must be adjusted according to the specific types and quantities of pollutants involved in the assessment (Ma et al 2020). However, existing studies mostly follow Hakanson's grading standard directly, that is, without any adjustments to (E) and (RI) (Workineh et al 2018;Zheng et al 2020), thus affecting the reliability of the evaluation results. In this study, the necessary adjustments are made.…”
Section: Introductionmentioning
confidence: 99%